2006
DOI: 10.1111/j.1467-940x.2006.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

International Tax Competition and Double Taxation

Abstract: This paper examines international tax competition, with respect to both corporate income tax rates and tax rules for double taxation. Unlike existing studies, this study assumes that governments set non‐discriminatory tax rates on domestic‐ and foreign‐sourced corporate income and can choose no tax allowance as the tax rule. Consequently, the Nash equilibrium outcomes contradict the intuition underlying previous studies: no tax allowance is chosen as the tax rule where world economic welfare can be maximized. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The effects of signing tax treaties were studied by Ida (2006), who demonstrated, contrary to other studies, that world economic well-being can be maximized through a zero-equilibrium tax rate within capital-exporting countries that earn various gains, while the importer states are registering losses, compared with the situation where there is no tax deduction. Barthel et al (2009) demonstrated that there is a direct link between international tax treaties and foreign investment, although in Davies et al (2009) on multinationals in Sweden, the impact is particularly small, there is the possibility of having subsidiaries in partner countries.…”
Section: Discussion and Recommendationsmentioning
confidence: 95%
See 1 more Smart Citation
“…The effects of signing tax treaties were studied by Ida (2006), who demonstrated, contrary to other studies, that world economic well-being can be maximized through a zero-equilibrium tax rate within capital-exporting countries that earn various gains, while the importer states are registering losses, compared with the situation where there is no tax deduction. Barthel et al (2009) demonstrated that there is a direct link between international tax treaties and foreign investment, although in Davies et al (2009) on multinationals in Sweden, the impact is particularly small, there is the possibility of having subsidiaries in partner countries.…”
Section: Discussion and Recommendationsmentioning
confidence: 95%
“…Some studies had provided some insights regarding the DTA and tax revenues. Ida (2006) made an empirical study in three stages. First, in the case of the government tax rule, the author used Nash equilibrium tax rules, second, in the case of corporate income tax rate was applied Nash equilibrium tax rate and, third, in the case of the capital market, was applied Capital market equilibrium.…”
Section: Double Taxation Conventions Evolutionmentioning
confidence: 99%